Cytokine expression in the brain in human cerebral malaria. - Brown, H; Turner, G; Rogerson, S; Tembo, M; Mwenechanya, J; Molyneux, M; Taylor, T (1999)
Evidence from clinical studies and murine models supports a role for cytokines in the pathogenesis of human cerebral malaria (CM). In this study, reverse transcriptase-polymerase chain reaction (RT-PCR) was used to investigate expression of mRNA for transforming growth factor (TGF)-beta, interleukin (IL)-1beta, and tumor necrosis factor (TNF)-alpha in human postmortem tissue. Immunohistochemistry was used to examine the distribution of cytokine protein. TGF-beta was expressed in normal brain, in CM, and in meningitis and encephalitis. IL-1beta was absent from normal brain but was detected in CM and other cerebral infections. TNF-alpha mRNA was expressed only in CM, although TNF-alpha protein was also seen in meningitis. Cytokine mRNA expression in the brain did not correlate with the density of parasitized erythrocytes detected using RT-PCR for major surface protein-2. This report of RT-PCR on postmortem human tissues infected with CM demonstrates induction of the proinflammatory cytokines TNF-alpha and IL-1beta in the brain.